Optimization of initial dosage of quetiapine in schizophrenic patients: effects of fluvoxamine or duloxetine coadministration - Chen, Xiao; Zhang, Yue; Yin, Di; Jin, Ying-Wei; He, Su-Mei; Liu, Chen-Xu; Zhang, Cun; Wang, Dong-Dong (Frontiers in Pharmacology, 2024)
Objective: Quetiapine was approved for use in schizophrenia patients, however individualized dosage regimen was unclear, especially when it came to drug-drug interactions (DDI). Thus, this study was to investigate potential DDI and initial dosage optimization of quetiapine in schizophrenia patients based on population pharmacokinetics (PPK). Methods: Ninety-six schizophrenia patients treated by quetiapine were included to establish PPK model, which including multiple co-administration drug. Results: Ultimately, weight, fluvoxamine or duloxetine co-administration affected quetiapine clearance in schizophrenia patients. Without fluvoxamine or duloxetine co-administration, 16, and 12 mg/kg/day quetiapine were recommended to schizophrenia patients with weights of 40-50, and 50-120 kg, respectively. With fluvoxamine co-administration, 8 mg/kg/day quetiapine was recommended to schizophrenia patients with weights of 40-120 kg. With duloxetine co-administration, 8 mg/kg/day quetiapine was recommended to schizophrenia patients with weights of 40-120 kg. With fluvoxamine and duloxetine co-administration simultaneously, 4 mg/kg/day quetiapine was recommended to schizophrenia patients with weights of 40-120 kg. Conclusion: The present study was the first time to investigate potential DDI and initial dosage optimization of quetiapine in schizophrenia patients based on PPK, and initial dosage of quetiapine in schizophrenia patients were optimizated based on fluvoxamine or duloxetine co-administration.